A review on the implementation of QLASSIC in construction projects - Syeh Ameer Ali, Syarifah Firdaus; Tan , Chin Keng; Yeoh, Kah Ching (IIUM Press, 2011)
Construction Industrial Development Board (CIDB) of Malaysia has established QLASSIC as a quality indicator in determining the quality level of construction projects. This paper reviews various aspects of the system including the definition, objectives, scope, component, and assessment. This review aims to create awareness on the system among various parties in the construction industry.